Geometric Analysis of the Gronggong – Beber Cirebon Highway STA 0+000 – STA 2+000 - Zahra, Muhammad Ryfqy Az; Syaputra, Febrian; Nurhalifa, Arrum; Isradi, Muhammad (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Road infrastructure is a vital component in regional development, serving as a means of transportation, economic driver, and connectivity enhancer. Inadequate design can cause problems such as traffic congestion and accidents. Therefore, this study aims to analyze road geometry, determine pavement thickness, and estimate project costs for the Gronggong–Beber road section in Cirebon Regency. The study location is the main road connecting Bukit Gronggong and Beber District, which has a gentle to moderate hilly topography. The data used includes the 2025 Average Daily Traffic (ADT) and design parameters with a design speed (Vr) of 70 km/h and a design life of 15 years. Based on calculations, the total Annual Average Daily Traffic (AADT) value is 8109.29 SMP/day, and the road type applied is 2/2-TT. The geometric analysis results show that of the five curves reviewed (C1, C2, C3, C4, C5), all require transition curves (Pcek > 0.25). The recommended curve type is Spiral–Circle–Spiral (S-C-S). For example, at Curve 1, the radius value used is R = 180 m (exceeding Rmin = 167.75 m), with a superelevation (ed) of 6.43% and a spiral curve length (Ls) of 74.10 m. Furthermore, the vertical alignment analysis at five PV points shows that the vertical curve length (Lv) taken is 42 m, based on the flexibility requirements. Overall, the geometric redesign of the road on the Gronggong–Beber section is necessary to ensure that the road meets safety and comfort standards in accordance with technical specifications.